Ponderomotive Generation and Detection of Attosecond Free-Electron Pulse Trains - Kozak, Martin; Schönenberger, Norbert; Hommelhoff, Peter (Physical Review Letters, 2018)
Atomic motion dynamics during structural changes or chemical reactions have been visualized by pico- and femtosecond pulsed electron beams via ultrafast electron diffraction and microscopy. Imaging the even faster dynamics of electrons in atoms, molecules, and solids requires electron pulses with subfemtosecond durations. We demonstrate here the all-optical generation of trains of attosecond free-electron pulses. The concept is based on the periodic energy modulation of a pulsed electron beam via an inelastic interaction, with the ponderomotive potential of an optical traveling wave generated by two femtosecond laser pulses at different frequencies in vacuum. The subsequent dispersive propagation leads to a compression of the electrons and the formation of ultrashort pulses. The longitudinal phase space evolution of the electrons after compression is mapped by a second phase-locked interaction. The comparison of measured and calculated spectrograms reveals the attosecond temporal structure of the compressed electron pulse trains with individual pulse durations of less than 300 as. This technique can be utilized for tailoring and initial characterization of suboptical-cycle free-electron pulses at high repetition rates for stroboscopic time-resolved experiments with subfemtosecond time resolutio